Fungus ball paranasal sinuses: pattern of histopathology and culture characteristics - Nugroho Suharsono (PERHATI-KL, 2019)
Background: Fungal infection of the nose and paranasal sinuses is an uncommon condition which is now being increasingly recognized. The clinical presentation is not specific with various symptoms such as nasal obstruction, purulent nasal discharge, facial pain, and chronic cough. Only unilaterality may alert the clinician. Purpose: To find the morphological characteristics of the fungus in patients with paranasal sinus fungus ball. Methods: A retrospective study of 13 paranasal sinus fungus balls cases which underwent endoscopic sinus surgery at Department of Otorhinolaryngology Head and Neck Surgery St. Vincentius A Paulo Hospital Surabaya from March, 2012 until December, 2013. Age, sex, histopathology and fungal cultur were analysed. Histopathologic sections of all the patients were stained with hematoxylin and eosin (H&E), and Gomori methenamine silver (GMS). The specimens were then cultured on Sabouraud dextrose agar plates and incubated at 30°C for 1 month. At the end of the incubation period, the samples were evaluated microscopically to detect fungi and identify their species. Results: The age reported of the 13 patients, was ranging from 36 to 63 years old. There was a significant female predominance, 10 female patients (76.92%) and 3 male patients (23.08%). Histopathological examination showed that most causative agents were Aspergillus species 92.31% (12/13). Culture test was positive for 69.23% (9/13). Aspergillus niger (61.54%, 8/13) is the most frequent fungus reported to cause fungus balls. Conclusion: Pattern of histopathologic on HE and GMS is very helpful and sensitive to identify fungi. The most common isolated mould in our study was Aspergillus niger.Keywords: fungus ball, histopathology and culture, Aspergillus nigerABSTRAK Latar Belakang: Infeksi jamur di hidung dan sinus paranasal merupakan kondisi yang jarang terjadi, namun kini lebih sering ditemukan. Gejala klinisnya tidak spesifik dapat berupa obstruksi hidung, sekret dari hidung, nyeri wajah, dan batuk kronis. Bila terjadi unilateral, patut diwaspadai oleh para klinisi. Tujuan: Untuk mengetahui karakteristik morfologi fungus yang didapati pada pasien sinusitis jamur yang kami teliti. Metode: Dilakukan penelitian retrospektif pada 13 pasien sinusitis jamur yang menjalani bedah sinus endoskopi di Departemen Otorinolaringologi-Kepala Leher Rumah Sakit St. Vincentius A Paulo Surabaya dari bulan Maret 2012 sampai dengan Desember 2013. Dilakukan analisis usia, jenis kelamin, histopatologi dan kultur jamur. Pewarnaan preparat histopatologi menggunakan Hematoxylin dan eosin (H&E) dan Gomori Methenamine Silver (GMS). Kemudian spesimen diletakkan pada piring agar Sabouraud dextrose, dan dilakukan inkubasi pada suhu 30°C selama satu bulan. Pada akhir masa inkubasi, sampel dievaluasi dengan mikroskop untuk mendeteksi jamur dan spesiesnya. Hasil: Didapati usia 13 penderita berkisar dari 36-63 tahun. Wanita lebih dominan sebanyak 10 penderita (76,92 %) dan 3 penderita laki-laki (23,08%). Hasil pemeriksaan histopatologi menunjukkan spesies Aspergillus sebagai penyebab utama (92,31%) pada 12 penderita (12/13).Tes kultur positif pada 69,23% (9/13). Jamur yang paling sering menyebabkan bola jamur pada sinus adalah Aspergillus niger (61,54%, 8/13). Kesimpulan: Pewarnaan preparat histopatologi menggunakan Hematoxylin dan eosin (H&E) dan Gomori Methenamine Silver (GMS) sangat berguna dan sensitif dalam mendeteksi adanya jamur. Jenis jamur yang paling banyak ditemukan pada penelitian kami adalah Aspergillus niger.